Sequential attachment and Listeria predominance under turbulent flow - Pant K; Palmer J; Flint S (Taylor and Francis Group, 2026)
The exploration of multispecies biofilms has provided significant insight into how bacteria interact in natural environments. However, crucial information is still lacking when the assumption that all the bacteria approach the substrate simultaneously during multispecies biofilm formation is challenged. The objective of this study was to analyse the multispecies biofilm formed by industrially relevant bacteria, including Pseudomonas fluorescens and Listeria monocytogenes, focusing on sequential colonisation under turbulent flow and static conditions. Under flow conditions, the attachment of Listeria on preformed Pseudomonas biofilm was significantly higher (p < 0.001) and reached its highest cell concentration (8.9 log CFU cm–2) earlier (by 24 h) compared to control (sterile stainless-steel surfaces) and co-inoculated (with P. fluorescens) conditions. The conditioning of stainless-steel surfaces with freeze-dried and rehydrated exopolysaccharides (0–27.5 µg ml–1) extracted from P. fluorescens did not affect L. monocytogenes attachment, indicating the importance of biofilm architecture. The cell concentration of P. fluorescens was not affected by either the flow rate or the colonisation order in a multispecies biofilm. Overall, the sequence of colonisation affects biofilm formation in multispecies biofilms under turbulent flow and is an important variable in studies of the community lifestyle of multispecies biofilms.
Keywords: Preformed biofilm; colonisation sequence; multispecies detachment; species predominance; spatial arrangement